Acrylic foam sealing tape

By using acrylic foam sealing tape in the battery pack of new energy vehicles, the problem of insufficient sealing performance of existing sealing strips in high temperature, high humidity and hot and cold impact environments is solved, and better sealing performance and battery safety are achieved.

CN119842328APending Publication Date: 2025-04-18江苏晶华新材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411576156.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The existing sealing strips are insufficient in the high temperature, high humidity and hot and cold impact environments of new energy vehicle battery packs, making it difficult to meet battery safety requirements.

Method used

Acrylic foam sealing tape is used, and its structure includes a release layer, acrylic pressure-sensitive adhesive layer, acrylic foam layer and TPU adhesive layer. The sealing performance is improved through specific raw material composition and layer structure design.

Benefits of technology

Under high temperature and high humidity and hot and cold impact aging conditions, the acrylic pressure-sensitive adhesive layer exhibits stable peel strength, strong tensile strength and high elongation of break, excellent compression recovery performance and water vapor sealing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure BDA0005121860660000021
    Figure BDA0005121860660000021
Patent Text Reader

Abstract

The invention discloses an acrylic foam sealing tape which comprises a release layer, an acrylic pressure-sensitive adhesive layer, an acrylic foam layer and a polyurethane adhesive layer which are sequentially arranged, and is characterized in that the acrylic foam layer is prepared from the following raw materials in parts by weight: 80-95 parts of first acrylic prepolymer, 2-10 parts of first functional monomer and 0.1-5 parts of second functional monomer, 0.05 to 6 parts of hollow glass beads, 0.05 to 2 parts of fumed silica, 0.01 to 5 parts of a first photoinitiator and 0.05 to 0.5 part of color paste. After the product is subjected to high-temperature and high-humidity aging, cold and hot impact aging, high-temperature and high-humidity, cold and hot impact aging, 0 DEG C brine ice and 60 DEG C serial experiments, the acrylic acid pressure-sensitive adhesive layer has stable peel strength, high tensile strength, high elongation at break, excellent compression recovery performance and excellent water vapor sealing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to an acrylic foam sealing tape. Background Art

[0002] At present, with the vigorous development of new energy vehicles, the safety performance requirements of batteries are becoming increasingly stringent. The sealing process and sealing strips of the battery pack frame play a decisive role in its safety.

[0003] The general sealing strip is made of rubber, and the waterproof grade is not high. The foamed silicone rubber sealing tape is an acrylic system. The sealing tape is a long and thin strip. When in use, the high-viscosity side of the sealing tape can effectively adhere to the surrounding of the box frame. The weak-viscosity side of the sealing tape contacts the sealing cover, and the adhesion is very low, which is easy to remove. For the heating of the battery, the sealing tape has good thermal aging performance; for the vehicle wading, it can ensure the sealing and waterproof performance within 30 minutes at a depth of 1m, improving the safety of the vehicle battery module.

[0004] Therefore, in view of the above-mentioned technical problems, it is necessary to provide an acrylic foam sealing tape.

[0005] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0006] The purpose of the present invention is to provide an acrylic foam sealing tape.

[0007] In order to achieve the above object, a technical solution provided by a specific embodiment of the present invention is as follows:

[0008] The acrylic foam sealing tape comprises a release layer, an acrylic pressure-sensitive adhesive layer, an acrylic foam layer and a polyurethane adhesive layer which are arranged in sequence. The raw materials for preparing the acrylic foam layer comprise, by weight, 80-95 parts of a first acrylic prepolymer, 2-10 parts of a first functional monomer, 0.1-5 parts of a second functional monomer, 0.05-6 parts of hollow glass microbeads, 0.05-2 parts of fumed silica, 0.01-5 parts of a first photoinitiator and 0.05-0.5 parts of a color paste.

[0009] In one or more embodiments of the present invention, the first functional monomer is selected from the group consisting of isodecyl acrylate, acrylic acid, hydroxyethyl acrylate, 1,6-hexanediol diacrylate, and dicyclopentadiene acrylate.

[0010] In one or more embodiments of the present invention, the second functional monomer is selected from the group consisting of: lauryl acrylate, hydroxyethyl acrylate, 1,6-hexanediol diacrylate, and dicyclopentadiene acrylate.

[0011] In one or more embodiments of the present invention, the hollow glass microspheres are FN-80GSD.

[0012] In one or more embodiments of the present invention, the fumed silica is Evonik R972.

[0013] In one or more embodiments of the present invention, the first photoinitiator is selected from: benzoin and its derivatives, benzil and its derivatives, acetophenone and its derivatives, and acylphosphine oxide photoinitiators.

[0014] In one or more embodiments of the present invention, the raw materials for preparing the first acrylic prepolymer include, by weight:

[0015]

[0016] In one or more embodiments of the present invention, the first soft monomer is selected from the group consisting of butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, isodecyl acrylate, lauryl methacrylate, and lauryl acrylate.

[0017] In one or more embodiments of the present invention, the third functional monomer is selected from the group consisting of: N,N-dimethylacrylic acid amide, 4-hydroxybutyl acrylate, 4-hydroxybutyl acrylate, and acrylic acid.

[0018] In one or more embodiments of the present invention, the second photoinitiator is selected from: 1-hydroxycyclohexylphenyl ketone, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0019] In one or more embodiments of the present invention, the chain transfer agent is selected from the group consisting of mercaptans, thioethers, dodecyl mercaptan, and carbon tetrachloride.

[0020] In one or more embodiments of the present invention, the release layer is selected from: polypropylene release film, polyolefin release film such as polyethylene, polyester release film such as polyethylene terephthalate.

[0021] In one or more embodiments of the present invention, the raw materials for preparing the acrylic pressure-sensitive adhesive layer include the following components in parts by weight:

[0022]

[0023] In one or more embodiments of the present invention, the fourth functional monomer is selected from: 1,6-hexanediol diacrylate, N,N-dimethylacrylic acid amide, 4-hydroxybutyl acrylate, 4-hydroxybutyl acrylate.

[0024] In one or more embodiments of the present invention, the third photoinitiator is selected from: 1-hydroxycyclohexylphenyl ketone, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0025] In one or more embodiments of the present invention, the silane coupling agent is selected from: KBM-403.

[0026] In one or more embodiments of the present invention, the raw materials of the second acrylic prepolymer include, by weight:

[0027]

[0028] In one or more embodiments of the present invention, the second soft monomer is selected from the group consisting of isooctyl acrylate, isodecyl acrylate, lauryl methacrylate, and lauryl acrylate.

[0029] In one or more embodiments of the present invention, the first hard monomer is selected from the group consisting of isobornyl acrylate, methyl methacrylate, and butyl acrylate.

[0030] In one or more embodiments of the present invention, the fifth functional monomer is selected from: 4-hydroxybutyl acrylate, cyclohexane, N,N-dimethylacrylic acid amide and ethyl 2,3-dichlorophenylacetate.

[0031] In one or more embodiments of the present invention, the fourth photoinitiator is selected from: 1-hydroxycyclohexylphenyl ketone, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

[0032] In one or more embodiments of the present invention, the chain transfer agent is selected from the group consisting of mercaptans, thioethers, dodecyl mercaptan, and carbon tetrachloride.

[0033] Compared with the prior art, the acrylic foam sealing tape of the present invention has an acrylic pressure-sensitive adhesive layer with stable peel strength, strong tensile strength and high elongation at break, excellent compression recovery performance, and excellent water vapor sealing performance after high temperature and high humidity aging, hot and cold shock aging, high temperature and high humidity, hot and cold shock aging, and 0°C ice salt water and 60°C serial experiments. DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0035] Embodiment 1

[0036] The acrylic foam sealing tape of the present embodiment comprises a release layer, an acrylic pressure-sensitive adhesive layer, an acrylic foam layer and a TPU adhesive layer which are arranged in sequence.

[0037] Release layer:

[0038] In this embodiment, there is no particular limitation on the thickness of the release layer, and in this embodiment of the present invention, a polyethylene (PE) release film is preferred.

[0039] Acrylic pressure-sensitive adhesive layer:

[0040] In this embodiment, the thickness of the acrylic pressure-sensitive adhesive layer is 50 microns. The raw materials for forming the acrylic pressure-sensitive adhesive layer include the following components, which are composed by weight: 100 parts of the second acrylic prepolymer, 0.2 parts of the fourth functional monomer 1,6-hexanediol diacrylate, 0.25 parts of the third photoinitiator 1-hydroxycyclohexyl phenyl ketone, and 0.3 parts of the silane coupling agent KBM-403.

[0041] Among them, the raw materials for preparing the second acrylic prepolymer include the following components, which are composed by weight: 70 parts of the second soft monomer isooctyl acrylate, 20 parts of the first hard monomer butyl acrylate, 10 parts of the fifth functional monomer cyclohexylamine, 0.1 parts of the fourth photoinitiator diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, and 0.01 parts of the chain transfer agent sulfur.

[0042] Acrylic foam layer:

[0043] In this embodiment, the thickness of the acrylic foam layer is not particularly limited. The raw materials for forming the acrylic foam layer include the following components, which are composed by weight: 90 parts of the first acrylic prepolymer, 10 parts of the first functional monomer acrylic acid, 0.3 parts of the second functional monomer 1,6-hexanediol diacrylate, 1.5 parts of hollow glass microspheres FN-80GSD, 0.5 parts of fumed silica Evonik R972, 0.3 parts of the first photoinitiator 1-hydroxycyclohexyl phenyl ketone, and 0.5 parts of color paste. The color pastes are all ordinary commercially available color pastes, such as blue color paste, red color paste, etc.

[0044] Among them, the raw materials for preparing the first acrylic prepolymer include the following components, which are composed by weight: 95 parts of the first soft monomer isooctyl acrylate, 5 parts of the third functional monomer acrylic acid, 0.1 parts of the second photoinitiator 1-hydroxycyclohexyl phenyl ketone, and 0.01 parts of the chain transfer agent thiol.

[0045] TPU layer:

[0046] In this embodiment, the thickness of the TPU glue layer is 10 microns, and TPU glue with a modulus of 30 is used.

[0047] Acrylic foam sealing tapes were prepared as described above, and 5 different groups were taken as samples to be tested.

[0048] A Room temperature peel strength test (electrophoretic steel interface):

[0049] The samples were cut into 8mm width and 150mm length for room temperature adhesion test.

[0050] B Aging peel strength test (6061 aluminum plate):

[0051] 1. Cut the sample into 8mm width and 150mm length, attach it to the test board and carry out aging at 85℃*85%RH*1000H. After aging, carry out the test.

[0052] 2. Cut the sample into 8mm wide and 150mm long, stick it on the test board and carry out hot and cold shock aging at -40℃~85℃*1000H. After aging, carry out the test.

[0053] C tensile strength test (-40℃, 25℃, 80℃):

[0054] 1. The sample is cut into 8mm width and 100mm length. The two ends of the sample strip are fixed with 25mm wide masking tape. The test gauge length is 50mm, and the room temperature tensile strength test is carried out.

[0055] D Low temperature brittleness test (-40℃):

[0056] 1. Cut the sample into 8mm width and 150mm length, put the sample into -40℃ refrigerator for 24 hours and then test it for low temperature brittleness test.

[0057] E Water vapor seal test:

[0058] Customize an aluminum container box (including lid) according to the aluminum battery packaging box for automobiles, stick a circle of sealing tape on the edge of the container, cover the lid and tighten the screws around it, and perform aging at 85℃*85%RH*1000H. Throw the container into a 1-meter-deep pool for 30 minutes and then fish it out. Place it in a constant temperature and humidity chamber for 24 hours, and remove the lid to check whether water has entered the container.

[0059] Customize an aluminum container box (including lid) according to the aluminum battery packaging box for automobiles, adhere a circle of sealing tape on the edge of the container, cover the lid and tighten the screws around it, and perform hot and cold shock aging at -40℃~85℃*1000H. Throw the container into a 1-meter-deep pool for 30 minutes and then fish it out. Place it in a constant temperature and humidity chamber for 24 hours, and remove the lid to check whether water has entered the container.

[0060] Customize an aluminum container box (including lid) according to the aluminum battery packaging box for automobiles, stick a circle of sealing tape on the edge of the container, cover the lid and tighten the screws around it, carry out aging at 85℃*85%RH*1000H, and then continue to carry out hot and cold shock aging at -40℃~85%RH*1000H. Throw the container into a 1-meter-deep pool of water for 30 minutes, then fish it out, and place it in a constant temperature and humidity chamber for 24 hours. Remove the lid and check whether water has entered the container.

[0061] The test results are shown in the following table:

[0062]

[0063]

[0064]

[0065] Embodiment 2

[0066] The acrylic foam sealing tape of the present embodiment comprises a release layer, an acrylic pressure-sensitive adhesive layer, an acrylic foam layer and a TPU adhesive layer which are arranged in sequence.

[0067] Release layer:

[0068] In this embodiment, there is no particular limitation on the thickness of the release layer, and in this embodiment of the present invention, a polyethylene (PE) release film is preferred.

[0069] Acrylic pressure-sensitive adhesive layer:

[0070] In this embodiment, the thickness of the acrylic pressure-sensitive adhesive layer is 50 microns. The raw materials for forming the acrylic pressure-sensitive adhesive layer include the following components, which are composed by weight: 100 parts of the second acrylic prepolymer, 0.1 parts of the fourth functional monomer 1,6-hexanediol diacrylate, 0.1 parts of the third photoinitiator 1-hydroxycyclohexyl phenyl ketone, and 0.15 parts of KBM-403.

[0071] Among them, the raw materials for preparing the second acrylic prepolymer include the following components, which are composed by weight: 80 parts of the second soft monomer isooctyl acrylate, 10 parts of the first hard monomer isobornyl acrylate, 10 parts of the fifth functional monomer N,N-dimethylacrylamide, 0.1 parts of the fourth photoinitiator diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide, and 0.01 parts of the chain transfer agent sulfur.

[0072] Acrylic foam layer:

[0073] In this embodiment, the thickness of the acrylic foam layer is not particularly limited, and the raw materials for preparing the acrylic foam layer include the following components, which are composed by weight: 95 parts of the first acrylic prepolymer, 5 parts of the first functional monomer 4-hydroxybutyl acrylate, 0.1 parts of the second functional monomer 1,6-hexanediol diacrylate, 3 parts of hollow glass microspheres FN-80GSD, 1 part of fumed silica Evonik R972, 0.3 parts of the first photoinitiator 1-hydroxycyclohexyl phenyl ketone, and 0.5 parts of color paste. The color pastes are all ordinary commercially available color pastes, such as blue color paste, red color paste, etc.

[0074] The raw materials for preparing the first acrylic prepolymer include the following components, which are composed by weight: 80 parts of the first soft monomer isooctyl acrylate, 20 parts of the third functional monomer acrylic acid, 0.5 parts of the second photoinitiator 1-hydroxycyclohexyl phenyl ketone, and 0.01 parts of the chain transfer agent thiol.

[0075] TPU layer:

[0076] In this embodiment, the thickness of the TPU glue layer is 10 microns, and TPU glue with a modulus of 30 is used.

[0077] Acrylic foam sealing tapes were prepared as described above, and 5 different groups were taken as samples to be tested.

[0078] A Room temperature peel strength test (electrophoretic steel interface):

[0079] The samples were cut into 8mm width and 150mm length for room temperature adhesion test.

[0080] B Aging peel strength test (6061 aluminum plate):

[0081] 3. Cut the sample into 8mm width and 150mm length, attach it to the test board and carry out aging at 85℃*85%RH*1000H. After aging, carry out the test.

[0082] 4. Cut the sample into 8mm width and 150mm length, stick it on the test board and carry out hot and cold shock aging at -40℃~85℃*1000H. After aging, carry out the test.

[0083] C tensile strength test (-40℃, 25℃, 80℃):

[0084] 1. The sample is cut into 8mm width and 100mm length. The two ends of the sample strip are fixed with 25mm wide masking tape. The test gauge length is 50mm, and the room temperature tensile strength test is carried out.

[0085] D Low temperature brittleness test (-40℃):

[0086] 1. Cut the sample into 8mm width and 150mm length, put the sample into -40℃ refrigerator for 24 hours and then test it for low temperature brittleness test.

[0087] E Water vapor seal test:

[0088] Customize an aluminum container box (including lid) according to the aluminum battery packaging box for automobiles, stick a circle of sealing tape on the edge of the container, cover the lid and tighten the screws around it, and perform aging at 85℃*85%RH*1000H. Throw the container into a 1-meter-deep pool for 30 minutes and then fish it out. Place it in a constant temperature and humidity chamber for 24 hours, and remove the lid to check whether water has entered the container.

[0089] Customize an aluminum container box (including lid) according to the aluminum battery packaging box for automobiles, adhere a circle of sealing tape on the edge of the container, cover the lid and tighten the screws around it, and perform hot and cold shock aging at -40℃~85℃*1000H. Throw the container into a 1-meter-deep pool for 30 minutes and then fish it out. Place it in a constant temperature and humidity chamber for 24 hours, and remove the lid to check whether water has entered the container.

[0090] Customize an aluminum container box (including lid) according to the aluminum battery packaging box for automobiles, stick a circle of sealing tape on the edge of the container, cover the lid and tighten the screws around it, carry out aging at 85℃*85%RH*1000H, and then continue to carry out hot and cold shock aging at -40℃~85%RH*1000H. Throw the container into a 1-meter-deep pool of water for 30 minutes, then fish it out, and place it in a constant temperature and humidity chamber for 24 hours. Remove the lid and check whether water has entered the container.

[0091] The test results are shown in the following table:

[0092]

[0093]

[0094] Comparative Example 1

[0095] The acrylic foam sealing tape of this comparative example comprises a release layer, an acrylic pressure-sensitive adhesive layer, an acrylic foam layer and a TPU adhesive layer which are arranged in sequence.

[0096] Release layer:

[0097] In this embodiment, there is no particular limitation on the thickness of the release layer, and in this embodiment of the present invention, a polyethylene (PE) release film is preferred.

[0098] Acrylic pressure-sensitive adhesive layer:

[0099] In this embodiment, the thickness of the acrylic pressure-sensitive adhesive layer is 50 microns. The raw materials for forming the acrylic pressure-sensitive adhesive layer include the following components, which are composed by weight: 100 parts of the second acrylic prepolymer, 0.5 parts of the fourth functional monomer 1,6-hexanediol diacrylate, 0.3 parts of the third photoinitiator 1-hydroxycyclohexyl phenyl ketone, and 0.5 parts of KBM-403.

[0100] Among them, the raw materials for preparing the second acrylic prepolymer include the following components, which are composed by weight: 60 parts of the second soft monomer isooctyl acrylate, 25 parts of the first hard monomer butyl acrylate, 15 parts of the fifth functional monomer cyclohexane, 0.1 parts of the fourth photoinitiator diphenyl-(2,4,6-trimethylbenzoyl)oxyphosphine, and 0.005 parts of the chain transfer agent sulfur.

[0101] Acrylic foam layer:

[0102] In this embodiment, the thickness of the acrylic foam layer is not particularly limited, and the raw materials for preparing the acrylic foam layer include the following components, which are composed by weight: 95 parts of the first acrylic prepolymer, 5 parts of the first functional monomer acrylic acid, 0.5 parts of the second functional monomer 1,6-hexanediol diacrylate, 6 parts of hollow glass microspheres FN-80GSD, 22 parts of fumed silica Evonik R97, 0.3 parts of the first photoinitiator 1-hydroxycyclohexyl phenyl ketone, and 1 part of color paste. The color pastes are all ordinary commercially available color pastes, such as blue color paste, red color paste, etc.

[0103] The raw materials for preparing the first acrylic prepolymer include the following components, which are composed by weight: 95 parts of the first soft monomer isooctyl acrylate, 5 parts of the third functional monomer acrylic acid, 0.1 parts of the second photoinitiator 1-hydroxycyclohexyl phenyl ketone, and 0.005 parts of the chain transfer agent thiol.

[0104] TPU layer:

[0105] In this embodiment, the thickness of the TPU glue layer is 10 microns, and TPU glue with a modulus of 30 is used.

[0106] Acrylic foam sealing tapes were prepared as described above, and 5 different groups were taken as samples to be tested.

[0107] A Room temperature peel strength test (electrophoretic steel interface):

[0108] The samples were cut into 8mm width and 150mm length for room temperature adhesion test.

[0109] B Aging peel strength test (6061 aluminum plate):

[0110] 5. Cut the sample into 8mm width and 150mm length, attach it to the test board and carry out aging at 85℃*85%RH*1000H. After aging, carry out the test.

[0111] 6. Cut the sample into 8mm width and 150mm length, stick it on the test board and carry out hot and cold shock aging at -40℃~85℃*1000H. After aging, carry out the test.

[0112] C tensile strength test (-40℃, 25℃, 80℃):

[0113] 1. The sample is cut into 8mm width and 100mm length. The two ends of the sample strip are fixed with 25mm wide masking tape. The test gauge length is 50mm, and the room temperature tensile strength test is carried out.

[0114] D Low temperature brittleness test (-40℃):

[0115] 1. Cut the sample into 8mm width and 150mm length, put the sample into -40℃ refrigerator for 24 hours and then test it for low temperature brittleness test.

[0116] E Water vapor seal test:

[0117] Customize an aluminum container box (including lid) according to the aluminum battery packaging box for automobiles, stick a circle of sealing tape on the edge of the container, cover the lid and tighten the screws around it, and perform aging at 85℃*85%RH*1000H. Throw the container into a 1-meter-deep pool for 30 minutes and then fish it out. Place it in a constant temperature and humidity chamber for 24 hours, and remove the lid to check whether water has entered the container.

[0118] Customize an aluminum container box (including lid) according to the aluminum battery packaging box for automobiles, adhere a circle of sealing tape on the edge of the container, cover the lid and tighten the screws around it, and perform hot and cold shock aging at -40℃~85℃*1000H. Throw the container into a 1-meter-deep pool for 30 minutes and then fish it out. Place it in a constant temperature and humidity chamber for 24 hours, and remove the lid to check whether water has entered the container.

[0119] Customize an aluminum container box (including lid) according to the aluminum battery packaging box for automobiles, stick a circle of sealing tape on the edge of the container, cover the lid and tighten the screws around it, carry out aging at 85℃*85%RH*1000H, and then continue to carry out hot and cold shock aging at -40℃~85%RH*1000H. Throw the container into a 1-meter-deep pool of water for 30 minutes, then fish it out, and place it in a constant temperature and humidity chamber for 24 hours. Remove the lid and check whether water has entered the container.

[0120] The test results are shown in the following table:

[0121]

[0122]

[0123]

[0124] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0125] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. An acrylic foam sealing tape, comprising a release layer, an acrylic pressure-sensitive adhesive layer, an acrylic foam layer, and a polyurethane adhesive layer arranged in sequence, characterized in that: The raw materials for preparing the acrylic foam layer include, by weight: 80-95 parts of a first acrylic prepolymer, 2-10 parts of a first functional monomer, 0.1-5 parts of a second functional monomer, 0.05-6 parts of hollow glass microspheres, 0.05-2 parts of fumed silica, 0.01-5 parts of a first photoinitiator, and 0.05-0.5 parts of a color paste.

2. The acrylic foam sealing tape according to claim 1, characterized in that: The first functional monomer is selected from the group consisting of isodecyl acrylate, acrylic acid, hydroxyethyl acrylate, 1,6-hexanediol diacrylate, and dicyclopentadiene acrylate.

3. The acrylic foam sealing tape according to claim 1, characterized in that: The second functional monomer is selected from the group consisting of: lauryl acrylate, hydroxyethyl acrylate, 1,6-hexanediol diacrylate, and dicyclopentadiene acrylate.

4. The acrylic foam sealing tape according to claim 1, characterized in that: The hollow glass microspheres are FN-80GSD.

5. The acrylic foam sealing tape according to claim 1, characterized in that: The fumed silica is Evonik R972.

6. The acrylic foam sealing tape according to claim 1, characterized in that: The first photoinitiator is selected from the group consisting of: 1-hydroxycyclohexyl phenyl ketone, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

7. The acrylic foam sealing tape according to claim 1, characterized in that: The raw materials for preparing the first acrylic prepolymer include, by weight:

8. The acrylic foam sealing tape according to claim 6, characterized in that: The first soft monomer is selected from the group consisting of butyl acrylate, isobutyl acrylate, 2-ethylhexyl acrylate, isodecyl acrylate, lauryl methacrylate, and lauryl acrylate.

9. The acrylic foam sealing tape according to claim 6, characterized in that: The third functional monomer is selected from the group consisting of: N,N-dimethylacrylic acid amide, 4-hydroxybutyl acrylate, 4-hydroxybutyl acrylate and acrylic acid.

10. The acrylic foam sealing tape according to claim 6, characterized in that: The second photoinitiator is selected from the group consisting of: 1-hydroxycyclohexyl phenyl ketone, diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.

11. The acrylic foam sealing tape according to claim 6, characterized in that: The chain transfer agent is selected from the group consisting of mercaptan, thioether, dodecyl mercaptan, and carbon tetrachloride.